Respect families’ right to commemorate loved ones killed during uprising without reprisals on one-year anniversary - Amnesty International (Amnesty International, 2023)
In new research, Amnesty International details how the Iranian authorities have been subjecting victims’ families to arbitrary arrest and detention, imposing cruel restrictions on peaceful gatherings at grave sites, and destroying victims’ gravestones.
Keywords: 2023-08 August

Ukraine: Russian court upholds 13-year sentence against Ukrainian human rights defender Maksym Butkevych - Amnesty International (Amnesty International, 2023)
An appeal hearing at a Moscow court on Tuesday (22 August) which has upheld the 13-year sentence imposed on Maksym Butkevych, a Ukrainian human rights defender, is a grave miscarriage of justice Amnesty International said today.
Keywords: 2023-08 August; Russia

Arbitrary detentions continue in Venezuela - Amnesty International (Amnesty International, 2023)
Venezuela: Arbitrary detentions continue as a tool of government control and repression. In the new report, Life detained: Politically motivated arbitrary detentions continue in Venezuela Amnesty International denounces the Nicolás Maduro.
Keywords: 2023-08 August

Lebanon: Comedian Arrested for Critical Jokes - Amnesty International (Amnesty International, 2023)
Lebanese authorities’ arrest and investigation of prominent comedian Nour Hajjar, solely in retaliation for his jokes, represents a new escalation in Lebanon’s crackdown on public criticism, the Coalition to Defend Freedom of Expression in Lebanon of which Amnesty International is a member, said today.
Keywords: 2023-08 August

Ugandan authorities must drop charges in death penalty case under Anti-Homosexuality Act - Amnesty International (Amnesty International, 2023)
It is deeply disturbing that the Ugandan authorities are prosecuting people based on their real or perceived sexual orientation or gender identity.
Keywords: 2023-08 August

“Death came to our home”. War crimes and civilian suffering in Sudan - Amnesty International (Amnesty International, 2023)
Sudan: War crimes rampant as civilians killed in both deliberate and indiscriminate attacks. Read the Report
Keywords: 2023-08 August